Mitos e formação continuada: olhares de professores sobre interdisciplinaridade e contextualização Na dimensão estética da educação - Negreiros, Eliana Costa da Cruz de (2009)
This study represents as a research topic the teachers´ continued formation and had as objective to identify and to study the high school teacher´s views about the concept of interdisciplinary and contextualization, keeping like reference the concepts brought by High School in Network - “Ensino Médio em Rede”- , developed by São Paulo State Educational Department – Secretaria da Educação do Estado se São Paulo - between 2004 and 2006. The theoretical review about the subject showed included the study of High School National Curricular Guidelines, promulgated in the year of 1998. To achieve the objectives of this research was realized a qualitative research, with narrative interviews questioning 05 (five) teachers who taught in 2008, in the High School segment, at “Teacher Loureiro Junior Public School”. From the theoretical reference of Lenoir (2007), Fazenda (2002), Josso (2004), Ferreira-Santos (2008), Brandão (1986) e Freire (1992) we investigated and analyzed the necessary aspect about continued formation, with special attention to the assumption that, in the school, such training needs to have as a guiding line the appointment of to take a look at the past and look at the knowledge present in the teachers´ life history, allowing the action produced by the results reflection and comprehension, as subjects in your singularity. The research sought elements to understand the high school teachers’ conceptions (public school) about concepts “interdisciplinary” and “contextualization” and the relation between the personal developments of such concepts with the life story, which led an assumption of a mitohermenêutica approach, for which not intended to search the truth or specific information, but the meaning construction, from inferences. The analysis favored the personal myths that emerge in the narratives of the person. The analysis results were really revealing and mentioned a considerable distance between witch is proposed by “High School in Network - “Ensino Médio em Rede”- , like public policies of teachers´ training, and what was, in fact, understood by teachers, noting the need of educational policies consider, in the teachers´ formation process, the esthetics dimension and the sensitivity, obtained from the (self) biographical narratives.